Prophetic Leadership Model for Public Bureaucracy: How It’s Works? - Syabibi, M. Ridho (UIN Fatmawati Sukarno Bengkulu, 2022)
This study discusses the prophetic leadership model and how to facilitate it in the public bureaucracy. Prophetic leadership is the ability possessed by leaders to influence subordinates under Islamic teachings (leading to the leadership pattern of the Prophet Muhammad). The research started by looking for reading sources (nash al-Qur'an, hadith, journals, and books), then interactive reading, making reading tables, and reducing the essence of reading before being transferred to a worksheet. The finding is that leadership can be explained through extrinsic and intrinsic motivation theory. Prophetic leadership includes inherent leadership because it uses spirituality as the basis of values. In Islam, prophetic leadership comes not only from intrinsic or ethical motivation but the integration of worldly motivations (Hashanah) and the hereafter (Salamah). So it is known that the trigger for prophetic leadership can result from imitating the Prophet Muhammad and social experience. The formation process took a long time, so it was concluded that prophetic leadership could be applied in the public bureaucracy if the state civil servants (ASN) has maturity in religion. Efforts to realize prophetic leadership can be started by analyzing the level of religious maturity. Bringing spiritual nuances into the organization is sufficient to facilitate ASN who have matured in religion. This study is in the analysis stage and predicts its application opportunities. Further researchers need to present best practice cases from this model. Formulating a measuring tool to assess the success of implementing prophetic leadership in the public bureaucracy is also important.